Variações interespecíficas no recrutamento de peixes migradores do alto rio Paraná : efeito da duração e época das cheias. - Oliveira, Anielly Galego de (2013)
We evaluated the relationship between the young of year abundance of different species of migratory fish and interannual variations in the duration and delay of floods. Abundance data were obtained from quarterly sampling in six floodplain lakes and three rivers of the Upper Paraná River floodplain, from March 2000 to December 2011, using gill nets of different meshes. Young of year of the species Brycon orbignyanus, Hemisorubim. platyrhynchos, Leporinus elongatus, Leporinus macrocephalus, Leporinus obtusidens, Pseudoplatystoma corruscans, Pterodoras granulosus, Prochilodus lineatus, Salminus brasiliensis and Sorubim lima were considered and daily water levels were provided by the Agência Nacional das Águas. Scatterplots were constructed to identify the trend between abundance of young of year of each species and duration or delay of floods. In addition were performed multiple regression analyzes using duration and delay as predictor variables. The results revealed differences in the responses of the species for the flood attributes despite all of them show a positive trend regarding the duration and negative in relation to the delay of flood. The species B. orbignyanus, L. elongatus, L. macrocephalus, L. obtusidens, P. lineatus e S. lima had positive exponential relationship with the duration of flood, and the most of species exhibited negative exponencial relationship with delay, excepting S. brasiliensis with linear trend. Nevertheless, the delay was selected as a significant predictor variable with duration only for L. elongatus, L. obtusidens, P. corruscans and P. lineatus. For these species, floods late can result in failure or incipient in recruitment because these species probably migrate early, in order to adjusts its energy reserves and swimming. Therefore, any effort to preserve the migratory fish species needs to consider manipulation of discharge released from reservoirs upstream of the study area. It is urgent that reservoirs be operated in order to release water in quantity, duration and timing compatible with the viability of spawning and survival of early forms of development of large migratory fish.